Theoretical study of combustion wave: Case of the generated wave in the methane and air combustion - Quispe, C. (2011)
In the present theoretical analysis, is described the occurrence of thermal shock wave that is produced by the located heat delivery. The general analysis is made considering that the physical properties of the flow changes when crossing this wave. Thus also, for practical cases; its observed that these properties vary slightly in an ample range of temperature, so also is analyzed the formation of this wave without variation of the physical properties of the flow; showing that in the flow only cannot appear dynamic shock waves, but also thermal shock waves.